A videoaula como instrumento pedagógico no ensino universitário: telessaúde em foco - Camargo, Wanderley Augusto Rodrigues (2015)
The video lecture has grown in importance in the educational setting, whether on the issue of technology availability, whether from a cultural point of view. This study examines the technical components necessary for the production of a video lecture that adequately meets the educational requirements for teaching. In a qualitative perspective were analyzed 12 video lectures produced by the Unisantos Telehealth Nucleus, used for the training of health professionals in the city of Praia Grande, SP. From theoretical framework for audiovisual production as well as pedagogical and educational, created a set of topics that guide the analysis of a video lecture. The videos were categorized into three different groups. In the first one, little-explored audiovisual resources transposing a face class approach to video. In the second group was created images script, role and content illustration showing them suitable technically. In the third, was concerned to place outside the studio recordings, but merely expository approach, resulting in interference in attention. These same videos were analyzed in another study were considered adequate by the students, despite the technical players. It was then found that the 12 produced video lectures were designed and planned within a pedagogical strategy. This sought to establish the relationship between course content that allowed a proper textual narrative to the student's reality. However, within the criteria of audiovisual language not exploited the potential of the video tool because the technical team not adhered to the characteristics displayed by this benchmark in this work, highlighting key elements to improve the transmitted message, as well as the facilitation of understanding of the contents by the viewer student of the video lectures.